ISOLATION AND IDENTIFICATION OF SEASONAL ENDOMYCOPHYTES OF INNER BARK OF CASTANOSPERMUM AUSTRALE A. CUNN AND C - T. G. NAGARAJA (The Bioscan, 2011)
Endophytic fungi from inner bark of Castanospermum australae A.Cunn and C were studied in three different season during 2009-2010. A total of 29 endophytes were recorded during rainy season, followed by 28 in winter season and 20 fungi in summer season. Aspergillus niger, A. flavus, Mucor sp., Fusarium oxysporum and Verticillium sp., were found to be dominant endophytes followed by Biospora punctata, Drechsclera sp., Nigrospora sp., Rhizophus stolonifer and Cladosporium species.